2019
DOI: 10.1080/09602011.2019.1620788
|View full text |Cite
|
Sign up to set email alerts
|

Good things better? Reappraisal and discrete emotions in acquired brain injury

Abstract: There has been substantial interest in emotion after acquired brain injury (ABI), but less attention paid to emotion regulation (ER). Research has focused primarily on the ER strategy of reappraisal for regulating negative emotions, without distinguishing between classes of emotion, and there has been no attempt at exploring these differences in patients with ABI.The present study explored components of reappraisal, across classes of emotion, and their associated neuropsychological mechanisms. Thirty-five pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 118 publications
4
19
1
2
Order By: Relevance
“…Although previous studies have shown that TBI might result in higher levels of impulsivity (Votruba et al, 2008), lower intelligence (Raymont et al, 2011), and impaired emotional processing or control (Rowlands et al, 2019), no differences were found in the current study. The detainees showed higher levels of impulsivity and lower intelligence when compared to nonincarcerated controls, but these differences are likely not the result of experienced TBI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have shown that TBI might result in higher levels of impulsivity (Votruba et al, 2008), lower intelligence (Raymont et al, 2011), and impaired emotional processing or control (Rowlands et al, 2019), no differences were found in the current study. The detainees showed higher levels of impulsivity and lower intelligence when compared to nonincarcerated controls, but these differences are likely not the result of experienced TBI.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients who have experienced a TBI may show deficits in various domains, including emotion processing, self-control, impulsivity, IQ, and aggression (Hartikainen et al, 2010;Levin & Hanten, 2005;Parker & Rosenblum, 1996;Wall et al, 2006). Reduced emotion regulation abilities following TBI have received relatively little attention but seems to be impaired after TBI (Rowlands et al, 2019). A decrease in such functions may result in erroneously interpreting situations in everyday life, and may impair problemsolving abilities through dialogue or negotiation, which in turn may increase the chance of violent and aggressive behavior (Leon-Carrion & Ramos, 2003).…”
mentioning
confidence: 99%
“…In particular, patients with brain injury took longer to generate a reappraisal (referred to as reappraisal difficulty), but when time was not considered they were able to produce a similar number of reappraisals (referred to as reappraisal productivity) to neurologically healthy controls (Salas et al, 2014). Extending on these findings, Rowlands et al (2019) found that patients with ABI were impaired across both reappraisal productivity and difficulty on an autobiographical recall reappraisal task, and reported less effective use of reappraisal to up-regulate positive emotions.…”
Section: Emotion Regulation After Brain Injurymentioning
confidence: 94%
“…In the second phase, the reappraisal needs to be maintained (using working memory), to shield it from the initial meaning (Kalisch, 2009). Recent evidence suggests that working memory may also play a role in the early phase, perhaps to keep the goal of reappraising in mind (Rowlands et al, 2019). Some inconsistencies are, however, notable in previous studies.…”
Section: Emotion Regulation After Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation